Self-Injurious Behavior in Child and Adolescent Psychiatry Inpatient Units: Actual Aspects of the Complex Care Provision - Lesinskienė, Sigita; Afrahi, Mariam; Pociūtė, Kamilė (Acta medica Lituanica, 2024)
Background: Nonsuicidal self-injurious behavior in children and adolescents is a major concern that requires mental health professionals’ attention. The aim of this study is to analyze clinical care aspects of children and adolescents who self-harm in psychiatric hospitals.Materials and methods: In 2023, 30 various specialists from five different child and adolescent psychiatric units in Lithuania were interviewed. The survey used a semistructured interview consisting of twelve questions related to complex clinical care methods of children and adolescents who self-harm. The interview responses were summarized and grouped into 5 categories: assessment and monitoring, methods and consequences of self-injury, safety measures, prevention and treatment, insights from staff.Results: Self-injurious behavior in psychiatric inpatient settings was managed through risk assessment, monitoring, communication, medication, counselling, removal of sharp objects, patient allocation, and a several of other methods such as safety contracts, rewards or alternate pain-inducing or self-harm mimicking stimuli. Despite the hospital’s safety procedures patients frequently devised alternate methods to self-harm, such as hitting and scratching themselves and using nonspecific materials.Conclusions: The management of self-harm in children and adolescents psychiatric settings remains insufficient. Further research is needed to explore alternative ways of managing self-injurious behavior in child and adolescent psychiatric hospitals.
Keywords: self-harm; inpatient units; clinical aspects; children; adolescents